1988
DOI: 10.1530/acta.0.1170497
|View full text |Cite
|
Sign up to set email alerts
|

A technique for superfusion of isolated granulosa cells. Dynamics of cAMP production and steroidogenesis in response to gonadotropins

Abstract: Abstract. A superfusion model for isolated ovarian cells was developed and characterized in detail. Granulosa cells isolated from pre-ovulatory rat ovarian follicles were placed in superfusion (perifusion) chambers with a volume of 125 μl. Culture medium was pumped through the chambers, collected in 20-min fractions of 600 μl and analysed for cAMP and steroids. Viability was confirmed by morphological examination. The use of polycarbonate membranes to retain the cells in the chambers was abandoned since the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Less frequent pulsatile administration of FSH at either concentration did not enhance SCC mRNA accumulation above basal. Our inferences regarding this molecular endpoint of FSH action are in agreement with previous functional studies that demonstrated that pulses of gonadotropins are more efficacious than continuous hormone exposure in increasing ovarian steroid production, follicular development, and luteinization [26][27][28][29][30]35]. The fractional increases in SCC mRNA accumulation observed here under perifusion conditions are consistent with the magnitude of the increases reported during static culture of porcine granulosa cells [36].…”
Section: Cyclic Amp Responsessupporting
confidence: 91%
See 2 more Smart Citations
“…Less frequent pulsatile administration of FSH at either concentration did not enhance SCC mRNA accumulation above basal. Our inferences regarding this molecular endpoint of FSH action are in agreement with previous functional studies that demonstrated that pulses of gonadotropins are more efficacious than continuous hormone exposure in increasing ovarian steroid production, follicular development, and luteinization [26][27][28][29][30]35]. The fractional increases in SCC mRNA accumulation observed here under perifusion conditions are consistent with the magnitude of the increases reported during static culture of porcine granulosa cells [36].…”
Section: Cyclic Amp Responsessupporting
confidence: 91%
“…This sustained responsiveness to FSH action contrasts sharply with the clear downregulation of cAMP release by cells perifused similarly but at 37 0 C. Furthermore, at 37 0 C the magnitude of the maximal rate of cAMP release decreased in granulosa cells receiving both the low-(100 ng/ml) and high-(600 ng/ml) concentration pulses of FSH. Other investigators have seen similar down-regulation of cAMP production after constant or repeated exposures to LH [34,35]. Woody and LaBarbera [32] and Ford and LaBarbera [48] reported that porcine granulosa cells remained responsive to pulses of FSH but desensitized after 4 h of constant administration of FSH.…”
Section: Cyclic Amp Responsesmentioning
confidence: 75%
See 1 more Smart Citation
“…An experimental model based on a perifusion technique offers advantages over static culture where frequent sampling of cellular secretions is difficult, substrates may become depleted, and metabolic products may accumulate and inhibit cellular activity. While other approaches to granulosa cell perifusion have been described (Johanson & Johanson, 1988), the use of cells attached to microcarriers reduces the technical difficulties associated with this technique. In this study, granulosa-luteal cells were perifused for periods of up to 14 h and still retained the ability to secrete progesterone in response to acute LH stimulation.…”
Section: Discussionmentioning
confidence: 99%